Molali, Surchandarja, Usebekistan: Die Arbeiten der Jahre 2012 und 2013 - Boroffka, Nikolaus (e-Forschungsberichte des DAI, 2023)
The settlement and burials of Molali, southern Uzbekistan, were discovered and partly studied in the early 1970s. They became eponymous for a stage of the Late Bronze Age although only few materials were published. Re-identified in 2010, an Uzbek-German team worked on the settlement in 2012 and 2013. The site was formerly located along 400–500 m on the right bank of a stream and had a width of ca. 200 m, much of which is destroyed or covered by the modern village. Three Bronze Age building phases and a Medieval cemetery could be excavated.